2016
DOI: 10.1007/s00234-016-1647-4
|View full text |Cite
|
Sign up to set email alerts
|

The plasticity of intrinsic functional connectivity patterns associated with rehabilitation intervention in chronic stroke patients

Abstract: The impact of rehabilitation intervention on intrinsic functional connectivity patterns throughout the brain was measurable on resting-state fMRI, and systematic assessment of resting-state functional connectivity can provide prognostic insight for later motor improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 45 publications
6
49
0
Order By: Relevance
“…Our connectivity analysis revealed dysfunction after subcortical lesions in the motor network. The most consistent finding in previous resting‐state studies is that patients with motor impairment after stroke show decreased interhemispheric connectivity of the ipsilesional M1 with the contralesional SMC (Park et al, ; Zheng et al, ). Compared to our previous M1‐based resting‐state FC study (Yin et al, ), although both studies enrolled stroke patients with a similar left motor pathway dysfunction, the FC changes in the pattern of the MN are somewhat different, which is possibly due to the adoption of different FC analysis methods.…”
Section: Discussionsupporting
confidence: 69%
“…Our connectivity analysis revealed dysfunction after subcortical lesions in the motor network. The most consistent finding in previous resting‐state studies is that patients with motor impairment after stroke show decreased interhemispheric connectivity of the ipsilesional M1 with the contralesional SMC (Park et al, ; Zheng et al, ). Compared to our previous M1‐based resting‐state FC study (Yin et al, ), although both studies enrolled stroke patients with a similar left motor pathway dysfunction, the FC changes in the pattern of the MN are somewhat different, which is possibly due to the adoption of different FC analysis methods.…”
Section: Discussionsupporting
confidence: 69%
“…A large number of studies had demonstrated the decreased FC between the bilateral M1s in patients following subcortical stroke (Grefkes et al, 2008; Park et al, 2011; Li Y. et al, 2016; Zheng et al, 2016), which were in line with our findings. Patients with subcortical stroke showed abnormalities in both function and structure (Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…One research from Li Y. et al (2016), who also performed the rsFC analysis of stroke patients after 1-month antiplatelet treatment, showed that the enhanced FC between the bilateral M1s after treatment following the motor function recovery and daily living abilities. Another two recent studies on the change of FC between the bilateral M1s after 4-week rehabilitation intervention in chronic stroke patients exhibited the same result (Fan et al, 2015; Zheng et al, 2016). Based on these previous studies, we can see that the adequate rehabilitation treatment could accelerate the recovery process in stroke patients, and the enhanced M1-M1 rsFC had been closely associated with motor function recovery (van Meer et al, 2012; Yin et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
“…[Insert Table 2 here] Of the training-related change studies, only one utilized EEG (Wu et al, 2015), whereas the remainder used the fMRI technique (Bajaj et al, 2015a, b;Fan et al, 2015; https://mc.manuscriptcentral.com/revneuro Neurosciences 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P r e v i e w O n l y 10 Laney et Lazaridou et al, 2013;Varkuti et al, 2013;Wadden et al, 2015;Zhang et al, 2016;Zheng et al, 2016).…”
Section: Training Studiesmentioning
confidence: 99%